The Fool - Mason, David, 1924-1974 (Salt Lake City, UT : Project Gutenberg, 2022)
"The Fool" by David Mason is a science fiction short story written in the mid-20th century. The narrative revolves around Duncan, an inept human teacher on a distant alien planet inhabited by the Tarchiki, a species known for their violent tendencies and brutal customs. The story explores themes of cultural misunderstanding, the folly of idealism, and the unintended consequences of one individual$1 (Bs actions within a foreign society. In this tale, Duncan, despite his failures and foolishness, attempts to instill Earthly morals and ethics into the Tarchiki, who find humor and absurdity in his teachings. His misguided efforts culminate tragically when he destroys their deity, Kachan, leading to his own death at the hands of a Tarchik high priest. In the aftermath, the Tarchiki, misinterpreting his last words as messages of forgiveness, erect a statue in his honor and adopt him as a new god, creating a religion around his silly antics and misguided ideals. This ironic twist highlights the disparity between Duncan$1 (Bs intentions and the realities of the Tarchiki's culture, illustrating the complexities and humorous absurdity of cross-cultural encounters. (This is an automatically generated summary.)s
Release date is 2022-02-25
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Human-alien encounters -- Fiction; Life on other planets -- Fiction; Religion -- Fiction